Bacterial Colonization on Ventilator Surfaces in the ICU of Government Hospital in Pontianak - Hariyanto IH; Putri, Icha Maidiana; Delima Fajar Liana (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: Colonization on ventilator surface is causing a risk of pathogenic bacteria transmission, leading to Healthcare-Associated Infections (HAIs). Therefore, this study aimed to determine bacterial colonization on ventilator surface in the Intensive Care Unit (ICU) of Government Hospital in Pontianak. Methods: Two ventilators, designated A and B, were sampled by sterile cotton swabs moistened with NaCl at 7 sampling points, namely power, interface, and control button, as well as screen, handrail, inspiratory port, and expiratory port. Samples were plated in triplication using the spread plate method on tryptone soya agar (TSA) medium and then incubated for 24 hours. The growth colonies were counted, and the morphology was observed macroscopically and microscopically. Results and Discussion: The results showed colonization at all sampling points on both ventilator surfaces. Ventilator A had total average number of colonies of 97, which was significantly higher compared to B with a total average of 7. Gram-negative bacteria (GNB) were observed more than Gram-positive bacteria (GPB) in both ventilators, accounting for 58.75% and 41.25%, respectively. The handrail part showed the highest number of colonies, accounting for 546 and 35 in ventilator A and B, respectively, represent both GNB and GPB but dominated by Gram-Positive coccus. The morphological forms of bacterial cells found were Gram-negative bacillus (GNB), Gram-positive coccus (GPC), Gram-negative coccus (GNC), and Gram-positive bacillus (GPB), with percentages of 37.50%, 27.50%, 21.25%, and 13.75%, respectively. Conclusion: This study showed colonization on the surfaces of two ventilators used in the ICU.